Thirty years in California; a contribution to the history of the state from 1849 to 1879. - Willey, Samuel H. (Samuel Hopkins), 1821-1914. (San Francisco, A.L. Bancroft & co., printers, 1879)
Samuel Hopkins Willey (1821-1914), a Presbyterian seminarian in Massachusetts, sailed to California as a home missionary in December 1848. He was a chaplain of the 1849 constitutional convention and served churches in San Francisco, Monterey, Santa Cruz, and Benecia. From 1862 to 1869 he headed the College of California at Berkeley, which was turned over to the University of California. Thirty years in California (1879) contains his recollections of Presbyterian congregations in Monterey and San Francisco and the founding of the Howard Presbyterian Church in Happy Valley. He describes religious and civil affairs in San Francisco through the 1850s and his role as head of the College of California.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- History; Ethnic groups -- California; Religion and ethics -- California